Filtration efficiency and differential pressure of fabrics used in non-medical masks based on SARS COVID-19 particle size. Issue 17 (September 2022) - Freeman, Charles; Burch, Reuben; Black, Catherine; Strawderman, Lesley; Rickert, Jaime; Wilson, John; Saucier, David; Smith, Brian
Non-medical fabric masks, recommended by the Centers for Disease Control and Prevention and the World Health Organization, are available in various fabrics. There is limited research on the overall effectiveness of fabrics used to make masks. The purpose of this study was to assess fabrics commonly used in non-medical masks against their ability to mitigate the spread of COVID-19 based on the size and throughput of aerosols and particles (<1 μ m). Seven different fabrics were evaluated on filtration efficiency (FE), differential pressure (dP), and filtration quality (Q factor). Results indicate <16% FE against particles the size of COVID-19, dP <0.51 in w.c., and Q factor <0.004 Pa −1 . FE results are lower than previously reported research with dP and Q factors within international guidelines. Using non-medical fabric masks as the sole mitigation strategy is not effective. It is critical to combine non-medical fabric masks with physical distancing to slow the spread of COVID-19 further.